Academic Stress Levels of Physical Education Students in Attending Odd Semester Classes 2021/2022 - Yarmani Yarmani; Yahya Eko Nopiyanto; Septian Raibowo; Dian Pujianto; Denny Pradana Saputro; M Fadli Dongoran (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2022)
The  purpose of this study was to determine the level of academic stress experienced by Physical Education students in the odd semester 2021/2022. This type of research was a quantitative approach using a descriptive method through a survey approach. The research sample consisted of 199 students whose samples were taken using random sampling. In this study, the instrument used was an academic stress scale questionnaire which the author compiled to be used as a measuring tool. This academic stress measurement tool uses a Likert scale. The validity of the instrument used was 0.85 while the reliability was 0.86. The description of academic stress will thoroughly explain the aspects of academic stress in the form of percentages and categories. The results of data analysis showed that the level of academic stress experienced by physical education students in attending the odd semester was in the moderate category, and there was no significant difference between the stress experienced by female and male students.